Fabrication and electrical characterization of solution-processed all-oxide transparent NiO/TiO2 p-n junction diode by sol-gel spin coating method - Cavas, M.; Gupta, R. K.; Al-Ghamdi, Ahmed. A.; Serbetci, Z.; Gafer, Zarah H.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Springer, 2013)
Solution-processed all-oxide transparent NiO/TiO2 p-n junction was fabricated using sol-gel spin coating method. The optical properties of the NiO and TiO2 films were studied by transmittance and absorbance spectra. The optical band gaps of NiO and TiO2 films were determined by optical absorption method and found to be 3.83 eV and 3.74 eV, respectively. The current-voltage characteristics of the oxides based p-n junction showed a rectifying behavior. The junction parameters such as ideality factor and barrier height were calculated using thermionic emission model, Chenug, and Norde method. The barrier height and ideality factor values of the diode were obtained to be 0.59 eV and 9.8, respectively.
Keywords: p-n junction; NiO; TiO2; Sol-gel; Thin films; Oxide semiconductor